Rehema's journey : a visit in Tanzania - Margolies, Barbara A., 1939- (New York : Scholastic, 1990)
Rehema, a nine-year-old girl who lives in the mountains of Tanzania, accompanies her father to Arusha City and visits the Ngorongoro Crater.
School Library Journal
Bulletin Of The Center For Children's Books
Kirkus Reviews
3.5
K-3
Keywords: Tanzania -- Description and travel -- 1981- -- Juvenile literature; Tanzania -- Description and travel; Tanzania -- Description and travel